Ecological niche selection shapes the assembly and diversity of microbial communities in Casuarina equisetifolia L. - Lin, Qi; Wang, Ying; Li, Miaomiao; Xu, Zhixia; Li, Lei (Frontiers in Plant Science, 2022)
The plant microbiome profoundly affects many aspects of host performance; however, the ecological processes by which plant hosts govern microbiome assembly, function, and dispersal remain largely unknown. Here, we investigated the bacterial and fungal communities in multiple compartment niches (bulk soil, rhizosphere soil, root endosphere, phylloplane, and leaf endosphere) of Casuarina equisetifolia L. at three developmental stages in Hainan Province, China. We found that microbiome assemblages along the soil–plant continuum were shaped by the compartment niches. Bacterial diversity and richness decreased from the soils to roots to leaves, with the highest network complexity found in the roots and the lowest found in the phylloplane. However, fungal diversity gradually increased from the soils to roots to phyllosphere, whereas fungal richness decreased from the soils to roots but increased from the roots to phyllosphere; the greatest network complexity was found in bulk soils and the lowest was found in the roots. Different biomarker taxa occurred in the different ecological niches. Bacterial and fungal communities exhibited distinct ecological functions; the former played important roles in maintaining plant growth and providing nutrients, whereas the latter predominantly decomposed organic matter. The bacterial community of C. equisetifolia mostly originated from bulk soil, whereas the fungal community was mainly derived from rhizosphere soil and air. Leaf endophytes were positively correlated with organic carbon, and root and soil microorganisms were positively correlated with total nitrogen, total phosphorus, and total potassium. Our findings provide empirical evidence for plant–microbiome interactions and contribute to future research on non-crop management and the manipulation of non-crop microbiomes.